Harnessing phage display technology for discovery of human IgGs targeting clinically relevant toxins from the venom of the Central American coral snake (Micrurus nigrocinctus) - Bermúdez Méndez, Erick (2019)
Envenomings caused by snakebites represent a serious public health problem in rural tropical areas of Africa, Asia, Latin America, and Oceania. Micrurus nigrocinctus, commonly known as Central American coral snake, is the most abundant and medically important species from the Elapidae family in Central America. The clinically most relevant toxins of M. nigrocinctus venom belong to the phospholipase A2 (PLA2) and three-finger toxin (3FTx) protein families. These toxins induce both myotoxic effects and potent neurotoxic effects that can lead to respiratory arrest due to neuromuscular paralysis. Currently, the only effective treatment available against bites from coral snakes consists of antivenom derived from serum of immunized horses. Although effective in neutralizing toxicity, this antivenom suffers from the drawbacks of having a heterologous nature and therefore being incompatible with the human immune system, difficult to manufacture due to the scarcity of M. nigrocinctus venom, and having a sub-optimally balanced response skewed towards venom components of high immunogenicity, but limited toxicity. In this project, we harness phage display technology to discover human single-chain variable fragments (scFvs) against key venom toxins of M. nigrocinctus venom. Following identification of high affinity binders employing the IONTAS scFv library, candidate scFv binders will be converted to the IgG format to increase their half-life, providing prolonged systemic protection against the venom. We expect this study will help to pave the way for the development of novel, low-cost antivenoms with improved efficacy and safety against M. nigrocinctus envenomings.